Analysis of factors that influence student preferences for online learning - Lilis Nurteti; Victor Benny Alexsius Pardosi; Mumu Muzayyin Maq; Saidatul Hanim; Jonris Tampubolon (Yayasan Adra Karima Hubbi, 2024)
Background. Online learning is a learning system that is not conducted face-to-face between teachers and students. Preference is a tendency made for one thing compared to another. Therefore, one's view on online learning will also vary. The quality and quantity of learning materials that are in accordance with the curriculum, standards, competencies, and student needs will differentiate students' preferences for online learning. Purpose This research aims to find out the reasons why students prefer online learning or not, and also to find out the factors that significantly influence the effectiveness of online learning. On the other hand, to analyse the appropriate strategy used in the use of media so that it is suitable for learning and can also be accessed by all individuals. Method. The method used in this research is quantitative. A method in which data is collected in the form of testable numbers. The data obtained is the number of responses. The data is obtained from the distribution of questionnaires containing questions regarding the analysis of factors affecting students' preferences for online learning. The statement presented in the questionnaire is a form of google form. The data will be processed through the oneway anova test on the SPSS application which was previously imported into excel. Results. The result of this study states that online learning can be done in schools. Online learning is also a way of learning without face-to-face in sharing information or communicating. Online learning has advantages and disadvantages depending on various factors that influence students' preferences for online learning. In addition, it also provides a strategic overview for teachers and students of the situation and what things will be prepared later. Conclusion This research can be concluded that the preference or choice of each student is different depending on how he/she views the subject. Online learning can be run effectively with good cooperation. Online learning will be implemented if there is support from all parties, be it students, teachers, parents, and even schools. Adjustment in learning is also easier for female students than male students.